Data associated with "Interpersonal relationships drive successful team science: an exemplary case-based study" - Love, Hannah; Cross, Jennifer; Fosdick, Bailey; Crooks, Kevin; VandeWoude, Susan; Fisher, Ellen (Colorado State University. Libraries, 2020)
Team science, or collaborations between groups of scientists with varying expertise, is required for researching solutions to complex problems of the 21st century. Despite the essential need for such transdisciplinary interactions, knowledge about training scientists and developing personal mastery, a set of principles and practices necessary for team learning, also referred to as the science of team science (SciTS) in productive team interactions is still in its nascent stages. This article reports on a longitudinal case study of an exemplary scientific team and evaluates the following question: How do scientists enhance their productivity through participation in transdisciplinary teams? Through a focused SciTS study applying mixed methods, including social network surveys, participant observation, focus groups, interviews, and historical social network data, we found that the interactions of an international, transdisciplinary scientific team trained scientists to become experts in their field, helped the team develop personal mastery, advanced their scientific productivity, and fulfilled the land grant mission. The team’s processes and practices to train new scientists propelled new ideas, collaborations, and research outcomes over a 15-year period. This case study highlights that in addition to specific scientific discoveries, scientific progress benefits from developing and forming interpersonal relationships among scientists from diverse disciplines.
Social network data collected on a scientific team 2015-2018.
Department of Fish, Wildlife, and Conservation Biology
Department of Sociology
Department of Microbiology, Immunology, and Pathology
Keywords: team science; exemplary case study; knowledge creation; social network analysis; personal mastery